Helical Electron Beam Status Online Evaluation for Magnetron Injection Gun - Wei Jiang; Chaoxuan Lu; Binyang Han; Boxin Dai; Qiang Zheng; Guo Liu; Jianxun Wang; Yong Luo (Quantum Beam Science, 2023)
The magnetron injection gun (MIG) is an essential component of the gyrotron traveling wave tube (gyro-TWT). Although the electron beam status influences the performance of the device, it cannot be measured directly in the experiment. An online evaluation module (OEM) for the experiment is developed to calculate the instant beam parameters of MIG. The OEM, by reconstructing the geometry of the MIG and related magnetic field distribution, can obtain the electron beam status under the operating parameters through the online simulation. The beam velocity spread of thermal emission with instant temperature and surface roughness are also considered. The validation is done in a W-band gyro-TWT, and the beam performance is evaluated in the experiment. With a pitch factor of 1.06 electron beam, the velocity spread affected by the electric-magnetic mismatch, thermal emission, and roughness is 1.00%, 0.56%, and 0.43%, respectively. The other beam parameters are also presented in the developed module. The OEM could guide and accelerate the testing process and ensure the safe and stable operation of the device.